Predicting factors of survival rates among alpha- and beta-thalassemia patients: a retrospective 10-year data analysis - Iam-arunthai, Kunapa; Suwanban, Tawatchai; Thungthong, Pravinwan; Chamnanchanunt, Supat; Fucharoen, Suthat (Frontiers in Hematology, 2024)
Thalassemia is a genetic hemoglobinopathy in which a defective globin chain can cause transfusion-dependent-anemia and complications. As genotype interactions lead to variations in the clinical course among thalassemia patients, clinical factors may help to predict survival in the types of thalassemia complicated by gene interactions.AIM: This study aims to determine clinical factors associated with survival in thalassemia patients. We retrospectively reviewed the medical records of thalassemia patients older than 15 years between 2002 and 2020 that were available at the Rajavithi hospital. Data on clinical parameters, laboratory tests, treatment, and survival status were collected and analyzed.Of the 478 thalassemia patients included, 68.8% were female, and the mean age was 41±17 years. The most common type of thalassemia is β-thalassemia (53.3%). Male, low body mass index, thalassemia type, comorbidities, low hemoglobin level, high ferritin level, and regular blood transfusion were significantly associated with short-term survival. However, only thalassemia type (β-thalassemia, p=0.048) and co-inheritance of α-and βthalassemia genotypes (p=0.03) were independently associated with death. The overall survival rates among patients with α-thalassemia, β-thalassemia, and co-inheritance α-and β-thalassemia genotypes were 98.1%, 90.6% and 75.0%, respectively. The death rate was 6.3%, and the most common cause of death was infection.Thalassemia genotype was a predictive factor of survival and co-inheritance of α-and βthalassemia genotypes resulting in a shorter-term survival compared with other types, especially transfusiondependent-thalassemia. These results can be applied in clinical settings to predict and possibly extend the life expectancy of thalassemia patients.